Development of patient‐reported outcome measures of children's oral health aesthetics. Issue 5 (10th August 2020) - Bevans, Katherine B.; Moon, Jeanhee; Becker, Brandon D.; Carle, Adam; Forrest, Christopher B.
Abstract: Objectives: To develop and evaluate the psychometric properties of child‐ and parent‐proxy measures of oral health aesthetics. Methods: Items that describe children's perceptions of their oral attractiveness and its impact on social, emotional, and behavioural functioning were developed based on a systematic review of existing measures, clinician feedback (n = 13) and child semi‐structured interviews (n = 27). The tools' content validity was assessed in cognitive interviews with 21 children. Items were administered to socio‐demographically diverse samples of 998 children aged 8‐17 years and 626 parents of children aged 5‐17 years. Psychometric methods were used to finalize and calibrate item banks, generate short questionnaire forms, and evaluate the tools' reliability, precision and validity. Results: The item banks and their short forms provide precise measurement across a wide range of oral health aesthetic states. They measure relevant and meaningful positive and negative experiences using terminology that most children as young as 8 years of age can understand. Known‐group comparisons and convergence with existing measures of oral health‐related quality of life, global health and body image provide evidence of construct validity. The scores are interpretable relative to the US general population. Conclusions: The oral health aesthetic item banks and short forms provide precise and valid assessments of children's satisfaction with their oral appearance. They may be useful for targeting and evaluating paediatric dental and orthodontic care in clinical practice and research settings.